Food from peace: breaking the links between conflict and hunger - Messer, Ellen; Cohen, Marc J.; D'Costa, Jashinta (International Food Policy Research Institute, 1998)
Creating a hunger-free world in the 21st century will require prevention and resolution of violent conflicts, as well as a concerted effort to rebuild war-torn societies. Between 1970 and 1990 violent conflicts led to hunger and reduced food production and economic growth in 43 developing countries. The reverse is also true, however: hunger and lack of access to basic necessities often lie at the root of violent conflicts. Conflict destroys land, water, biological, and social resources for food production, while military expenditures lower investments in health, education, agriculture, and environmental protection. Conflict leads to food insecurity through such deliberate acts as sieges of cities, stripping of victims’ assets, destruction of markets, elimination of health care, and breakup of communities. Other consequences of war are less intentional: people, including farmers and pastoralists, lose their livelihoods when workplaces become inaccessible. Once conflict ends, land mines must be removed, water systems refurbished, trees replanted, housing rebuilt, and communities revitalized. Without essential food and infrastructure, fragile peace can easily revert to conflict. Food and economic insecurity and natural resource scarcities—real and perceived—also can be major sources of conflict. Breaking the links between hunger and conflict must become a goal of food, agricultural, environmental, and economic development policy. For the international community this will entail paying closer attention to relief of food insecurity that can lead to conflict; delivery of development aid in ways that prevent competition leading to conflict; distribution of essential food aid in ways that do not prolong conflict; and special attention to reconstruction assistance. The authors end the brief with policy recommendations and suggestions for further research.